2022
DOI: 10.15826/chimtech.2022.9.1.03
|View full text |Cite
|
Sign up to set email alerts
|

Features of -C-C- coupling of quinoxaline-2-one with ethyl acetoacetate under acid catalysis

Abstract: Quinoxalin-2-one (1) reacts with ethyl acetoacetate in trifluoroacetic acid (TFA) to form 3-(2-oxopropylideno)-3,4-dihydroquinoxaline-2-one (2) and 3-(3-oxo-3,4- dihydroquinoxaline-2-(1H)-ylidene)methylquinoxaline-2-(1H)-one (3). The reaction product 3 was also obtained by heating the compound 1 with acetone in the presence of TFA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…In recent years, quinoxalin-2(1 H )-one has been prominently studied [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Furthermore, the direct acid-catalyzed C–H bond functionalization of quinoxalin-2(1 H )-one based on a nucleophilic aromatic substituted hydrogen approach (S N H -reaction) is of equal interest [ 25 , 26 , 27 , 28 , 29 ]. Several reviews summarize the C-3 functionalization of quinoxalin-2(1 H )-one and were published between 2019 and 2021 [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, quinoxalin-2(1 H )-one has been prominently studied [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Furthermore, the direct acid-catalyzed C–H bond functionalization of quinoxalin-2(1 H )-one based on a nucleophilic aromatic substituted hydrogen approach (S N H -reaction) is of equal interest [ 25 , 26 , 27 , 28 , 29 ]. Several reviews summarize the C-3 functionalization of quinoxalin-2(1 H )-one and were published between 2019 and 2021 [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…method for the synthesis of quinoxalin-2(1H)-one derivatives, and a large number of studies have appeared in this field in recent years [24][25][26][27][28][29][30][31][32][33][34][35]. A Web of Science search revealed that the number of papers related to quinoxalin-2(1H)-one has increased year by year over the last five years, with a total of 25 in 2018, 57 in 2019, 61 in 2020, 92 in 2021, and 95 in 2022.…”
Section: Introductionmentioning
confidence: 99%
“…Quinoxalin-2(1 H )-ones have a wide range of applications in materials science as well ( Scheme 2 ) [ 22 , 23 ]. The direct C–H functionalisation of quinoxalin-2(1 H )-one at the C3 position is the most cost-effective method for the synthesis of quinoxalin-2(1 H )-one derivatives, and a large number of studies have appeared in this field in recent years [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. A Web of Science search revealed that the number of papers related to quinoxalin-2(1 H )-one has increased year by year over the last five years, with a total of 25 in 2018, 57 in 2019, 61 in 2020, 92 in 2021, and 95 in 2022.…”
Section: Introductionmentioning
confidence: 99%